Modelling tourism expenditure using complexity theory - Olya, Hossein G. T.; Mehran, Javaneh (Elsevier Science Inc, 2017)
This study contributes to the literature by offering a novel analytical approach to solving complex interactions of tourism expenditure antecedents, advancing the theoretical reasoning behind the way in which socioeconomic indicators of prosperity combine to explain tourism expenditure on an international scale. The study explored a variety of configurations sufficient for simulation of both high and low scores of outbound tourism expenditures that have policy implications in both destination countries and countries of origin. We used complexity theory and fuzzy set qualitative comparative analysis (fsQCA) to analyze a composite score of 5-year data for 105 countries. The predictive validity results indicated the capacity of the proposed model to predict future outcome using other samples. The results expand our knowledge of the asymmetrical relationships of tourism expenditure and its antecedents.(C) 2017 Elsevier Inc. All rights reserved.
Keywords: Expenditure; Prosperity; Configuration; fsQCA; Predictive validity; Asymmetrical relationships